(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Problems related to students making mistakes in programming courses, students not completing their studies on time and students not experiencing an increase in their cumulative achievement index, are still frequently encountered among students in the Management Study Program. Program, Faculty of Economics and Business, University of Timor. This community service aims to ensure that academic supervisors can understand and use these guidelines as support in the academic guidance of each of their student supervisors. The methods used in this activity were lectures, discussions and questions and answers and a final survey was held as material for evaluating the activity to determine participants’ understanding after carrying out this socialization. This socialization was carried out in one of the lecture rooms of the FEB UNIMOR Management Study Program by explaining the contents of the academic guidance guidelines and explaining the importance of using academic guidance guidelines in supporting the effectiveness and efficiency of the implementation of academic guidance. in the Management Study Program, Faculty of Economics and Business, University of Timor. This activity was attended by 23 PA Management Study Program lecturers. The results of this service activity are very useful in supporting the implementation of effective and efficient academic guidance where lecturers know what the academic guidance mechanism is like, guidance time, academic guidance objectives and increase the knowledge and attitudes of PA lecturers in Management. The Study Program carries out academic guidance with students and is expected to be able to change, reduce the number of students who make mistakes in programming their courses, assist lecturers in guiding students so that more students complete their studies on time, assist PA lecturers in guiding their students so that their achievement index increases cumulative.